Spatial transactions and vernacular architecture of a nupe community in central Nigeria - Muhammad, Isa Bala (Penerbit UTM Press, 2015)
Vernacular architecture has been a subject of interest by scholars in different fields, views and perspectives. Some of such studies are on material, climate, morphology cultural behaviour and spatial needs of the people. The inclination of this research is on cultural behaviour and the use of space. This is because people’s cultural behaviour forms the foundation of vernacular architecture. However, most scholarly interests are focused on major ethnic groups with little interest on the minority ethnic group such as the Nupe ethnic group in Nigeria. Culture differs and so do the behaviour and the spatial needs of people. For a sustainable development to be attained, architecture needs to be tailored towards the cultural needs of the people. This study, therefore, embarked upon an ethnographic study to determine the basic domestic architectural spatial needs of the Nupe people, which entailed and eight months stay with the local people. The process of data elicitation included behavioural mapping and the conduct of interviews. A conclusion is drawn showing three spaces to be the most valued in the daily transactions of the Nupe community. They are zhempa, (courtyard) katamba (entrance hall) and kata (bedroom). The finding also showed that the values of spaces are not solely tied to tangible spatial utilization but also to intangible non spatial cultural values.